Variation in essential oil constituents of coriander (Coriandrum sativum L.) germplasm across coriander growing regions in India. Issue 2 (4th March 2022) - Saxena, S. N.; Swarup Meena, R.; Vishal, M. K.; John, S.; Kumar Sharma, L.; Mishra, B. K.; Agarwal, D.
ABSTRACT: Variations in essential oil composition of 148 coriander ( Coriandrum sativum L.) germplasms collected from various geographical locations in India were evaluated. Essential oil content was ranging from 0.04 to 0.27%. Eleven major compounds including α-pinene, camphene, β-pinene, myrcene, cymene, γ-terpinene, linalool, 4-allyl anisole, geraniol, anethole and geranyl acetate were detected in all the germplasm lines, with linalool as most abundant compound ranged from 16.59% to 96.69%. Another predominant compound observed was geranyl acetate, content of which ranged between 0.085 - 60.95%. Terpenoids consisting of α-pinene, β-pinene, camphene, myrcene, cymene and γ-terpinene accounted for up to 13.32% of essential oil. A significant negative correlation (r−0.811) was observed between linalool and geranyl acetate. Further, the germplasms were grouped in different classes as per major essential oil constituents. Cluster analysis was done using Ward's method based on the value of linalool, α-pinene, γ-terpinene and geranyl acetate, resulted in 10 distinct groups of germplasms.